A prisão em flagrante e as balizas constitucionais - Coelho, Francisco Neves (2010)
The present work approaches the flagrante delicto arrests analysing them under the principles established in 1988 s Brazilian s Federal Constitution. This work is divided in eleven chapters. Chapter 1 discourses on the principles, theirs distinction between rules and constitutional principles applied on arrest in flagrante delicto. Chapter 2 deals with the arrest in its several species highlighting preventive custody and temporary arrests. Chapter 3 presents the concept of flagrante delicto arrest, its judicial nature and historic evolution in the Brazilian s legal system. The variety in species of flagrante delicto arrests are presented in chapter 4 and its particular characteristics and considerations are in chapter 5. The convicted felon of flagrante delicto arrest is studied on chapter 6 and the constitutional assurance of this particular kind of arrest is treated in chapter 7. Chapter 8 discourses on legal documents of flagrante delicto arrest and chapter 9 is about the convicted felon presentation s to the designated judge. The legal exam of this specie of arrest is studied in chapter 10. And considerations about flagrante delicto arrests based on the Project of Brazilian s New Criminal Code are discoursed on chapter 11. Then, the conclusions on the studied subject are composed